Participants’ perspectives of “NeuroSask: Active and Connect”—a virtual chronic disease management program for individuals with a neurological condition - Stephen E. Patrick; Katherine B. Knox; Charity Evans; Michael Levin; Michael Levin; Gary Linassi; Ilia Poliakov; Alex Rajput; Sarah J. Donkers (Frontiers in Neurology, 2024)
IntroductionNeurological conditions account from more than half of Canadians requiring chronic care. Both physical activity and the development of a self-management skillset are critical components supporting individuals with chronic health conditions. “NeuroSask: Active and Connected” is a virtual chronic disease management program offering twice weekly neuro-physiotherapist directed “active” exercise sessions, followed by weekly knowledge-exchange “connect” sessions with invited guest experts. NeuroSask was launched April 2020 in response to the restricted services and supports for people with neurological conditions. The program aimed to provide seated physical activity, social interaction, and access to expertise in neurological conditions and neurorehabilitation. A program evaluation of NeuroSask was conducted to gain participants’ perspectives.MethodsAll participants registered for the NeuroSask program were invited to complete optional online surveys (SurveyMonkey) circulated by email at 3 occasions post-program launch: 10 weeks, 1 year, and 2 years. Participants could complete any one or all of the surveys, at their discretion. The number of potential respondents changed dependent on the total number of participants registered for NeuroSask at the time the survey was circulated. Questions were co-designed by multi-stakeholder team members. Descriptive statistics were used for closed-ended questions and a reflexive thematic analysis was completed with coding conducted in NVivo 12 Plus for open-ended text.ResultsResponse rates (participants/registrants) were as follows: 10-week survey 260/793, one year survey 326/1224, and 2-year survey 434/1989. 90% of participants reported being in either the age categories of 40–59 years or above 60 years. 75% of both survey respondents and program registrants were female. 70% of both survey respondents and program registrants reported a diagnosis of multiple sclerosis and 30% reported other neurological conditions. Survey respondents were from all ten Canadian provinces, with 45% reporting living outside of large cities. Respondents reported preferring online vs. in person format for this type of programming. Three main themes, and eight corresponding subthemes were identified highlighting the perceived impact and key components of the NeuroSask program: Theme 1 “together in a positive and encouraging environment” (subthemes 1a: connection, 1b: empowerment); Theme 2 “access to enthusiastic qualified leaders from home” (subthemes 2a: leader characteristics, 2b: accessibility, 2c: program logistics); Theme 3 “being able to enjoy everyday life” (subthemes 3a: symptom benefits and beyond, 3b: carry-over, 3c: keep going, please do not cancel).ConclusionNeuroSask is an example of an accessible and meaningful virtual approach to providing ongoing support for some individuals with neurological conditions. It was perceived as beneficial for fostering community and connection in a positive environment with perceived benefits extending beyond symptom management to participant reported improvements in function, daily life, and disease experience.